2014
DOI: 10.1242/bio.20148367
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast arrestin-related trafficking adaptor, Arn1/Any1, is ubiquitinated by Pub1 E3 ligase and regulates endocytosis of Cat1 amino acid transporter

Abstract: The Tsc1–Tsc2 complex homologous to human tuberous sclerosis complex proteins governs amino acid uptake by regulating the expression and intracellular distribution of amino acid transporters in Schizosaccharomyces pombe. Here, we performed a genetic screening for molecules that are involved in amino acid uptake and found Arn1 (also known as Any1). Arn1 is homologous to ART1, an arrestin-related trafficking adaptor (ART) in Saccharomyces cerevisiae, and contains a conserved arrestin motif, a ubiquitination site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 52 publications
4
50
0
Order By: Relevance
“…It has been reported that the Pub1 ubiquitin ligase and its arrestin-related adaptor, Any1, negatively regulate the plasma-membrane localization of amino acid transporters through endocytosis and their retention to Golgi/endosomes ( Nakase et al, 2013 ; Nakashima et al, 2014 ). The pub1∆ and any1∆ mutations partially suppressed the growth defect of the gtr1∆ and iml1∆ mutants on YES medium and abrogated their resistance to the toxic amino acid analogs, implying ameliorated amino-acid uptake in the double mutants ( Figure 7D ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Pub1 ubiquitin ligase and its arrestin-related adaptor, Any1, negatively regulate the plasma-membrane localization of amino acid transporters through endocytosis and their retention to Golgi/endosomes ( Nakase et al, 2013 ; Nakashima et al, 2014 ). The pub1∆ and any1∆ mutations partially suppressed the growth defect of the gtr1∆ and iml1∆ mutants on YES medium and abrogated their resistance to the toxic amino acid analogs, implying ameliorated amino-acid uptake in the double mutants ( Figure 7D ).…”
Section: Resultsmentioning
confidence: 99%
“…The study of the subcellular localization of the Bul1/Bul2 proteins may provide important information in this regard. Interestingly, recent studies in the evolutionary distant yeast Schizosaccharomyces pombe also point to a role of the arrestin-related protein Any1 (also named Arn1) in transporter trafficking at multiple places in the cell ( Nakase et al, 2013 ; Nakashima et al, 2014 ). Finally, data on the ART protein Aly2 suggest both a role in endocytosis and endosomal recycling depending on the transporter or the physiological condition considered ( Hatakeyama et al, 2010 ; O'Donnell et al, 2010 ; Crapeau et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In S. pombe , the arrestin-like protein Any1/Arn1 regulates endocytosis of amino acid transporters, and its PPXY motif interacts with the ubiquitin ligase Pub1 ( Nakase et al. , 2013 ; Nakashima et al. , 2014 ).…”
Section: Discussionmentioning
confidence: 99%